Efektivitas Massage Effleurage dan Teknik Relaksasi terhadap Tingkat Nyeri Punggung Ibu Hamil Trimester III di Puskesmas Kenali Besar Kota Jambi - Suryani Suryani; Ika Murtiyarini; Herinawati Herinawati; Romauli Romauli (Jurnal Akademika Baiturrahim Jambi, 2022)
Back pain is one of the most frequently reported complaints by pregnant women, varying from 50% to 70%, even 8% of them result in severe disability. Back pain is described as one of the minor disorders in pregnancy and is one of the causes of the incidence of cesarean delivery. From the initial survey, it was found that 4 out of 6 third trimester pregnant women had back pain complaints. The purpose of this study was to determine the effectiveness of Massage Effleurage and Relaxation Techniques on back pain in third trimester pregnant women at Kenali Besar Health Center Jambi City in 2021. This study was a quasi-experimental study using a two group pre-test and post-test design approach. The population of this study was 78 pregnant women in the third trimester using purposive sampling technique, the sample in this study used the SLOVIN formula so that a sample of 66 people was obtained. In the Mann-Whitney test for the effectiveness of Massage Effleurage and Relaxation Techniques, p value = 0.094 (p >0.05) which shows statistically there is no difference in average between Massage Effleurage and Relaxation Techniques on the level of back pain in third trimester pregnant women